БНХАУ-ын Өвөр Монголын Өөртөө Засах Орны эдийн засгийн хөгжлийн тойм - Ч, Батцэцэг (Journal of International Studies, 2004)
English title: Economic review of Inner Mongolian Autonomous territory of the PRC